Alternative pathways: struggling readers utilize art elements for listening/viewing comprehension and artistic response - Opat, Annie M. (Kansas State University, 2008)
Children who struggle in reading must be offered additional pathways of communication in order to enable them the opportunity to express themselves and enhance listening/viewing comprehension. Through understanding of the elements of art, the utilization of artistic response, and exposure to distinctive literature such as Caldecott Medal picture books, students are better equipped to grasp both visual and textual meaning. The purpose of this qualitative case study was to investigate the convergence of the elements of art, artistic response, and Caldecott Medal picture books and how they influence the listening/viewing comprehension of the struggling reader. Two, forty-minute lessons were given exclusively about the seven elements of art prior to the listening/viewing of Caldecott picture books. Participants engaged in the listening/viewing of six selected Caldecott Medal picture books through an initial listening/viewing within a small group setting, a second listening /viewing followed by an individual interview, and a third listening/viewing combined with an artistic response to each Caldecott picture book in a small group setting. General questioning concerning both story elements and elements of art were asked during both the initial listening/viewing and artistic response. Specific questioning occurred during the individual interview. Data were collected through interview and discussion transcriptions, visual and audio taped group work, field notes, and actual artistic response artwork. Data analysis revealed the enrichment of listening/viewing comprehension of the participants through 1) verbal usage of the elements of art, 2) comments regarding the elements of the story- setting, characters, events, problem, solution, 3) discussion of topics relating to personal experiences, 4) the dialogue of art media and the importance of art, and 5) distinct qualities of the picture book message theme articulated through artistic response. Art opened up the world of expression for the nine participants in this qualitative case study. Through the elements of art and artistic response combined with Caldecott literature, children were able to convey knowledge through an alternative pathway in order to enhance their listening/viewing comprehension of the picture books. Furthermore, documented evidence of the motivation of the participants indicated the value of exploration of rich literature and creative expression through artistic representation.
Keywords: Struggling readers; Artistic response; Art elements; Alternative communication; Education, Reading (0535)